The Effect of Self-Efficacy and Job Resources on Work Engagement: A Case Study of Correctional Officers in Pathumthani Province - Ploenaksorn, Patcharin; Petchsawang, Pawinee (Business Administration and Management Journal Review, 2023)
The purposes of this research are; 1) to study a level of self-efficacy, job resources, and work engagement. 2) to study a relation between self-efficacy and work engagement. 3) to study a relation between job resources and work engagement. 4) to study an effect of self-efficacy and job resources on work engagement. The sample were 276 employees of the correction department. This research employs a quantitative research method by selecting the sample group with quota sampling and accidental sampling technique. The research instruments were the questionnaire. The data were analysed by using frequency, percentage, mean, standard deviation, correlation analysis, and multiple regression analysis. The research findings are summarized that the level of self-efficacy, job resources, and work engagement are in high level. Self-efficacy and job resources positively correlates with work engagement at the statistically significant level of .01. The multiple regression analysis shows that self-efficacy, autonomy, and supervisory coaching positively affect work engagement at the statistically significant level of .05. In addition, these variables are significant predictors for work engagement with predictability of 34%.